Transition metal carbide doped material and preparation method thereof

By doping transition metal carbides, the order of its crystal structure is changed, and the problem of limited performance of existing catalysts is solved, and the effect of improving catalytic activity and oxidation resistance is achieved.

CN119433604APending Publication Date: 2025-02-14UNIV OF SHANGHAI FOR SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411584436.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The performance of existing transition metal carbide catalysts is limited by the excessive adsorption of hydrogen by molybdenum atoms and the formation of surface oxide layers, resulting in low catalytic activity and short service life.

Method used

By doping transition metal carbides, doped metals such as platinum, palladium, ruthenium, etc. are introduced to change the long-range order of their crystal structure, reduce the order of the structure, and thereby regulate catalytic activity and oxidation resistance.

Benefits of technology

It improves the intrinsic catalytic activity of transition metal carbides, slows down the oxidation rate, extends the service life of the catalyst, and reduces the demand for precious metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433604A_ABST
    Figure CN119433604A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and relates to a transition metal carbide doped material and a preparation method thereof, and the crystal structure of the doped transition metal carbide is amorphous or has a certain long-range disorder degree. The preparation process of the doped transition metal carbide material comprises the following steps: mixing a carbon-containing precursor, a transition metal precursor and a doped metal precursor, roasting at high temperature in a reducing atmosphere, and cooling to room temperature to obtain the doped transition metal carbide nano material. Compared with the prior art, by doping and introducing other doping elements, the long-range order degree of the crystal structure of the transition metal carbide is reduced, the electronic structure of the transition metal carbide is regulated and controlled, then the catalytic activity of the transition metal carbide is improved, and meanwhile the oxidation resistance of the transition metal carbide material is improved; and formation of a transition metal carbide surface oxide layer is slowed down.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a doped transition metal carbide material and a preparation method thereof. Background Art

[0002] Transition metal carbides (mainly carbides formed by transition metals such as Mo, W, Cu, Fe, Ni, Co, etc.) have excellent mechanical properties, chemical stability, ultra-high hardness, high melting point and good electrical conductivity. They have broad application prospects in coatings, aerospace, catalysis, energy conversion and storage (Journal of Materials Chemistry A, 2016, 4, 10379-10393). Taking molybdenum carbide for hydrogen evolution reaction as an example, it has an electronic structure similar to that of metal platinum and high corrosion resistance in strong acids and alkalis, making it an ideal catalyst to replace precious metal catalysts (Advanced Materials, 2023, 35, 2209954). However, the performance of molybdenum carbide-based catalysts is still limited by the excessive adsorption of hydrogen by molybdenum atoms, which makes hydrogen desorption difficult and limits the intrinsic catalytic activity of molybdenum carbide (Nature Communications, 2021, 12: 4018). In addition, an inert oxide layer is easily formed on the surface of molybdenum carbide. The formation of this thin oxide layer will significantly reduce the conductivity of the carbide material and also reduce its catalytic activity in the hydrogen evolution reaction.

[0003] In addition, amorphous materials have a higher defect site density and unique electronic structure than crystalline materials, thus possessing a large number of active sites and higher intrinsic catalytic ability, which makes them have lower reaction energy barriers in many catalytic reactions. However, there are currently no reports on disordered carbides and their preparation methods.

[0004] Therefore, how to further regulate the electron distribution of transition metal carbides, prepare amorphous transition metal carbides, enhance their intrinsic catalytic ability, slow down the oxidation of transition metal carbides, maintain stability, and extend the service life of carbide catalysts remains a difficult problem. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a doped transition metal carbide material and a preparation method thereof, so as to enhance the intrinsic catalytic ability of the transition metal carbide, improve the anti-oxidation ability of the carbide, and extend the service life of the carbide catalyst.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The invention provides a doped transition metal carbide material, which comprises transition metal carbide and doped metal. Calculated by mass percentage, the mass of the doped metal is 0.1% to 50% of the mass of the transition metal carbide, preferably 5% to 30%.

[0008] Furthermore, after doping, the long-range order of the crystal structure of the transition metal carbide changes, and the order decreases by 0.1%-100%.

[0009] Furthermore, the long-range order of the crystal structure of the transition metal carbide changes after doping, and the order is reduced by 50%-100%.

[0010] Furthermore, the doping metal is selected from at least one of platinum, palladium, ruthenium, iridium, gold, rhodium, osmium, silver, and chromium; and the transition metal in the transition metal carbide is selected from at least one of molybdenum, iron, cobalt, nickel, vanadium, copper, zinc, tungsten, and tin.

[0011] The present invention also provides a method for preparing any of the above-mentioned doped transition metal carbide materials, comprising the following steps: mixing a carbon-containing precursor, a transition metal precursor and a doped metal precursor, subjecting the mixture to a high-temperature roasting process, and then cooling the mixture to room temperature to obtain the doped transition metal carbide material.

[0012] Furthermore, the carbon-containing precursor is selected from any one of natural carbon materials, artificial carbon materials, various derived carbon materials or carbon-containing organic matter, such as Ketjenblack EC-600JD, Vulcan XC-72, glucose (C6H 12 O6) etc.; the transition metal precursor is selected from any one of transition metal sulfates, transition metal chlorides, transition metal acetates, transition metal nitrates, transition metal amines, transition metal carbonyl compounds, and transition metal oxides; the doped metal precursor is selected from any one of doped metal nitrates, doped metal chlorides, doped metal acetates, or doped metal sulfates.

[0013] Furthermore, the carbon-containing precursor, the transition metal precursor and the doping metal precursor are uniformly mixed by at least one of grinding, impregnation, ultrasonic mixing or rotary evaporation.

[0014] Furthermore, the solvent used in the immersion method, ultrasonic mixing method and rotary evaporation method is selected from at least one of water, ethanol, methanol, acetone, ethylene glycol or isopropanol.

[0015] Furthermore, the conditions of the high temperature calcination process are: calcination at 400°C to 1200°C for 0.5h to 48h in a specific atmosphere; the specific atmosphere is selected from any one of hydrogen, carbon monoxide, or a reducing mixed atmosphere.

[0016] Furthermore, the reducing mixed atmosphere includes reducing gas and balancing gas, wherein the volume concentration of the reducing gas is 5%-45%; the reducing gas is selected from any one of hydrogen or carbon monoxide, and the balancing gas is selected from any one of argon, nitrogen, and helium.

[0017] Furthermore, the method of cooling to room temperature is any one of natural cooling, rapid cooling and programmed cooling; the cooling rate of the programmed cooling method is 0.5°C / min to 20°C / min.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention provides a doped transition metal carbide material and a preparation method thereof. When there is a large difference in atomic size and the number of valence electrons between the doping element and the transition metal element in the original transition metal carbide, the periodicity and symmetry of the original crystal structure will be destroyed, resulting in structural disorder. This difference will cause lattice distortion, thereby affecting the electronic structure and physical and chemical properties of the material. In addition, the introduction of doping elements may produce local stress fields in the crystal structure, which will also cause local distortion of the lattice, thereby affecting the order of the entire crystal structure; this distortion may promote the transition between different phases, thereby making the crystal structure more disordered. The present invention performs a doping treatment on the transition metal carbide, so that the crystal structure of the transition metal carbide changes from order to disorder, and the order is reduced by 0.1%-100%.

[0020] (2) The doped transition metal carbide material provided by the present invention regulates the intrinsic catalytic ability of the transition metal by introducing the doped metal, thereby improving the catalytic activity of the carbide material while reducing the demand for precious metals.

[0021] (3) The doped transition metal carbide material provided by the present invention slows down the oxidation rate of the transition metal by introducing other metals, thereby improving the oxidation resistance and stability of the material and extending the service life of the doped material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD diagram of Mo2C prepared in Comparative Example 1 of the present invention;

[0023] Figure 2 XRD pattern of Ru / Mo2C(3-12) prepared in Example 1 of the present invention;

[0024] Figure 3 TEM image of Ru / Mo2C(3-12) prepared in Example 1 of the present invention;

[0025] Figure 4is the XRD pattern of Ir / Mo2C prepared in Example 2 of the present invention;

[0026] Figure 5 is the XRD pattern of Ru / WC prepared in Example 3 of the present invention;

[0027] Figure 6 is the XRD pattern of Pt / Mo2C prepared in Example 4 of the present invention;

[0028] Figure 7 is the XRD pattern of Cr / Mo2C prepared in Example 5 of the present invention;

[0029] Figure 8 is the XRD spectrum of Ru / Mo2C(1-14) prepared in Example 8 of the present invention;

[0030] Fig. 9 1 is a polarization curve diagram of Ru / Mo2C (3-12) prepared in Example 1 of the present invention and Mo2C prepared in Comparative Example 1;

[0031] Fig.10 Electrochemical polarization curves of Ru / Mo2C (3-12) prepared in Example 1 of the present invention and Mo2C prepared in Comparative Example 1 before and after the oxidation resistance test. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0033] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0034] The present invention provides a doped transition metal carbide material, which includes a transition metal carbide and a doping metal. In terms of mass percentage, the mass of the doping metal is 0.1% to 50% of the mass of the transition metal carbide, preferably 5% to 30%. The doping metal is selected from at least one of platinum, palladium, ruthenium, iridium, gold, rhodium, osmium, silver, and chromium; the transition metal in the transition metal carbide is selected from at least one of molybdenum, iron, cobalt, nickel, vanadium, copper, zinc, tungsten, and tin. After doping, the long-range order of the crystal structure of the transition metal carbide changes, and the order is reduced by 0.1% to 100%. Further, the order is reduced by 50% to 100%.

[0035] The above-mentioned doped transition metal carbide material is prepared by the following method:

[0036] The carbon-containing precursor, transition metal precursor and doped metal precursor are mixed, subjected to a high temperature roasting process, and then cooled to room temperature to obtain a doped transition metal carbide material. The carbon-containing precursor is selected from any one of natural carbon materials, artificial carbon materials, various derived carbon materials or carbon-containing organic matter; the transition metal precursor is selected from any one of transition metal sulfates, transition metal chlorides, transition metal acetates, transition metal nitrates, transition metal ammonium salts, transition metal carbonyl compounds, and transition metal oxides; the doped metal precursor is selected from any one of doped metal nitrates, doped metal chlorides, doped metal acetates or doped metal sulfates.

[0037] In some specific embodiments, the carbon-containing precursor, the transition metal precursor and the doping metal precursor are uniformly mixed by at least one of grinding, impregnation, ultrasonic mixing or rotary evaporation. The solvent used in the impregnation, ultrasonic mixing and rotary evaporation is selected from at least one of water, ethanol, methanol, acetone, ethylene glycol or isopropanol.

[0038] In some specific embodiments, the conditions of the high temperature calcination process are: calcination at 400°C to 1200°C for 0.5h to 48h in a specific atmosphere; the specific atmosphere is selected from any one of hydrogen, carbon monoxide, or a reducing mixed atmosphere. The reducing mixed atmosphere includes a reducing gas and a balance gas, wherein the volume concentration of the reducing gas is 5% to 45%; the reducing gas is selected from any one of hydrogen or carbon monoxide, and the balance gas is selected from any one of argon, nitrogen, and helium.

[0039] In some specific embodiments, the method of cooling to room temperature is selected from at least one of natural cooling, rapid cooling and programmed cooling; the cooling rate of the programmed cooling method is 0.5°C / min to 20°C / min.

[0040] Comparative Example 1

[0041] This comparative example provides a Mo2C material, and the specific steps are as follows:

[0042] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, dissolve 0.033g molybdenum pentachloride (MoCl5) in 1.6mL ethanol solution, and mix ultrasonically for 2h. The obtained viscous mixture sample is placed in a vacuum oven at 70°C and dried for 12h to obtain a solid mixture. The solid mixture is ground into powder and calcined at 800°C for 2h in a tubular furnace in an atmosphere of hydrogen and argon mixed gas (containing 5% hydrogen) with a heating rate of 10°C / min. When the temperature naturally drops to room temperature, the solid powder obtained is Mo2C material.

[0043] like Figure 1As shown, Figure 1 It is the XRD spectrum of the Mo2C material prepared in this comparative example. Figure 1 It can be found that all diffraction peaks correspond to the standard diffraction peaks of molybdenum carbide (PDF#35-0787). Among them, the diffraction peaks of 34.3°, 37.9°, and 39.3° appear in the range of 30° to 40°, which correspond to the (100), (002), and (101) crystal planes of molybdenum carbide, respectively, indicating that the molybdenum carbide material was successfully prepared in this comparative example.

[0044] Example 1

[0045] This embodiment provides a Ru / Mo2C(3-12) material, and the specific steps are as follows:

[0046] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, dissolve 0.033g molybdenum pentachloride (MoCl5) and 0.0062g ruthenium trichloride (RuCl3·3H2O) in 1.6mL anhydrous ethanol solution, and mix them ultrasonically for 2h. The viscous mixture sample is placed in a vacuum oven at 70°C and dried for 12h to obtain a solid mixture. The solid mixture is ground into powder and calcined at 800°C for 2h in a tubular furnace in a hydrogen-argon mixed gas (containing 5% hydrogen) atmosphere with a heating rate of 10°C / min. When the temperature naturally drops to room temperature, the solid powder obtained is Ru / Mo2C(3-12) material.

[0047] The mass percentage of the elements is calculated according to the amount of substance of the elements. It is assumed that the mass of the carbon-containing precursor (Ketjenblack EC-600JD) remains unchanged before and after annealing. The mass of Mo2C and Mo is calculated according to the amount of substance of Mo in MoCl5, and the mass of Ru is calculated according to the amount of substance of Ru in RuCl3. The mass percentage of Mo = the mass of Mo / (the total mass of Mo, Ru and Ketjenblack EC-600JD); the mass percentage of Ru = the mass of Ru / (the total mass of Mo, Ru and Ketjenblack EC-600JD).

[0048] The mass percentage of doped metal Ru in the Ru / Mo2C(3-12) material obtained in this embodiment is 4.70%, and the mass percentage of transition metal Mo is 17.84%. In this embodiment, the mass of doped metal Ru is 24.78% of the mass of transition metal carbide Mo2C.

[0049] like Figure 2 As shown, Figure 2 The XRD spectrum of the Ru / Mo2C(3-12) material prepared in this example. Figure 2 It can be found that there is no diffraction peak corresponding to Mo2C. Figure 1 Compared with the results of , the disappearance of the diffraction peak indicates that the crystal structure of molybdenum carbide is in an amorphous state. The above results show that ruthenium doping significantly reduces the structural order of molybdenum carbide. Based on the calculation based on Jade software, it is found that the structural order is reduced by about 98%.

[0050] like Figure 3 As shown, Figure 3 This is the TEM image of the Ru / Mo2C(3-12) material prepared in this example. Figure 3 It can be seen that the size of the prepared Ru / Mo2C(3-12) nanoparticles is 3nm~5nm.

[0051] Example 2

[0052] This embodiment provides an Ir / Mo2C material, and the specific steps are as follows:

[0053] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, dissolve 0.033g molybdenum pentachloride (MoCl5) and 0.012g chloroiridic acid (H2IrCl6·6H2O) in 1.6mL anhydrous ethanol solution, mix by ultrasonic for 2h, and place the obtained viscous mixture sample in a vacuum oven at 70℃ and dry for 12h to obtain a solid mixture. Grind the solid mixture into powder, and calcine it at 800℃ for 2h in a tube furnace under a hydrogen-argon mixed gas (containing 5% hydrogen) at a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the solid powder obtained is Ir / Mo2C material.

[0054] The calculation method is the same as that of Example 1. The mass percentage of doped metal Ir in the Ir / Mo2C material obtained in this example is 8.57%, and the mass percentage of Mo is 17.11%. The mass of doped metal Ir in this example is 47.14% of the mass of transition metal carbide Mo2C.

[0055] like Figure 4 As shown, Figure 4 This is the XRD spectrum of the Ir / Mo2C material prepared in this embodiment. Figure 4 It can be found that the diffraction peak intensity of the (002) and (101) crystal planes of Mo2C has decreased significantly, and the relative intensity of the two has also changed significantly. Figure 1 Compared with the results of , the decrease in the diffraction peak intensity indicates that the crystal structure order of MoC is significantly reduced, which indicates that Ir doping significantly reduces the structural order of MoC. Calculations based on Jade software show that the structural order is reduced by about 89%.

[0056] Example 3

[0057] This embodiment provides a Ru / WC material, and the specific steps are as follows:

[0058] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, dissolve 0.048g tungsten hexachloride (WCl6) and 0.0062g ruthenium trichloride (RuCl3·3H2O) in 1.6mL of anhydrous ethanol solution, mix by ultrasonic for 2h, and place the obtained viscous mixture sample in a vacuum oven at 70℃ and dry for 12h to obtain a solid mixture. Grind the solid mixture into powder, and calcine it at 800℃ for 2h in a tube furnace in a hydrogen-argon mixed gas (containing 5% hydrogen) atmosphere, with a heating rate of 10℃ / min, and wait for the temperature to naturally drop to room temperature to obtain a solid powder of Ru / WC material.

[0059] The calculation method is the same as that of Example 1. The mass percentage of doped metal Ru in the Ru / WC material obtained in this example is 4.04%, and the mass percentage of W is 29.38%. The mass of doped metal Ru in this example is 12.90% of the mass of transition metal carbide WC.

[0060] like Figure 5 As shown, Figure 5 The XRD spectrum of the Ru / WC material prepared in this embodiment is shown in FIG. Figure 5 It can be found that there is no diffraction peak corresponding to WC. The above results show that the doping of ruthenium significantly reduces the structural order of tungsten carbide. Based on the calculation of Jade software, it is found that the structural order is reduced by about 94%.

[0061] Example 4

[0062] This embodiment provides a Pt / Mo2C material, and the specific steps are as follows:

[0063] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, dissolve 0.038g molybdenum pentachloride (MoCl5) and 0.041g chloroplatinic acid (H2PtCl6·6H2O) in 1.6mL ethylene glycol solution, mix by ultrasonic for 2h, and place the obtained viscous mixture sample in a vacuum oven at 70℃ and dry for 12h to obtain a solid mixture. Grind the solid mixture into powder, and calcine it at 800℃ for 2h in a tube furnace in a hydrogen-hydrogen-argon mixed gas atmosphere (containing 5% hydrogen) at a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the solid powder obtained is Pt / Mo2C material.

[0064] The calculation method is the same as that of Example 1. The mass percentage of doped metal Pt in the Pt / Mo2C material obtained in this example is 2.98%, and the mass percentage of Mo is 20.54%. The mass of doped metal Pt in this example is 13.67% of the mass of transition metal carbide Mo2C.

[0065] like Figure 6 As shown, Figure 6 As shown, Figure 6 The XRD spectrum of the Pt / Mo2C material prepared in this embodiment is shown in FIG. Figure 6 It can be found that the diffraction peaks corresponding to Mo2C have disappeared, and no crystal diffraction peaks of molybdenum carbide or Pt are found. Figure 1 In comparison, the disappearance of the corresponding diffraction peak of molybdenum carbide indicates that its crystal structure is destroyed and becomes amorphous. The above results show that platinum doping significantly reduces the structural order of molybdenum carbide. Calculations based on Jade software show that the structural order is reduced by about 97%.

[0066] Example 5

[0067] This embodiment provides a Cr / Mo2C material, and the specific steps are as follows:

[0068] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, dissolve 0.033g molybdenum pentachloride (MoCl5) and 0.006g chromium trichloride (CrCl3·6H2O) in 1.6mL ethanol solution, mix by ultrasonic for 6h, and place the obtained viscous mixture sample in a vacuum oven at 70℃ for 12h to obtain a solid mixture. Grind the solid mixture into powder, and calcine it at 800℃ for 2h in a tube furnace in a hydrogen-hydrogen-argon mixed gas atmosphere (containing 5% hydrogen) at a heating rate of 10℃ / min. When the temperature naturally drops to room temperature, the solid powder obtained is Cr / Mo2C material.

[0069] The calculation method is the same as that of Example 1. The mass percentage of doped metal Cr in the Cr / Mo2C material obtained in this example is 2.47%, and the mass percentage of Mo is 18.25%. The mass of doped metal Cr in this example is 12.75% of the mass of transition metal carbide Mo2C.

[0070] like Figure 7 As shown, Figure 7 The XRD spectrum of the Cr / Mo2C material prepared in this embodiment is shown in FIG. Figure 7 It can be found that the diffraction peak corresponding to Mo2C basically disappears. Figure 1 In contrast, the disappearance of the corresponding diffraction peak of molybdenum carbide indicates that its crystal structure is destroyed and becomes amorphous. The above results show that platinum doping significantly reduces the structural order of molybdenum carbide. Calculations based on Jade software show that the structural order is reduced by about 94%.

[0071] Example 6

[0072] This embodiment provides a Ru / Mo2C material, and the specific steps are as follows:

[0073] Take 0.05g Vulcan XC-72 in a 20ml sample bottle, dissolve 0.033g molybdenum pentachloride (MoCl5) and 0.0020g ruthenium trichloride (RuCl3·3H2O) in 1.6mL anhydrous ethanol solution, mix by ultrasonic for 2h, and place the obtained viscous mixture sample in a vacuum oven at 70℃ and dry for 12h to obtain a solid mixture. Grind the solid mixture into powder, and roast it at 700℃ for 8h in a tube furnace with hydrogen and nitrogen mixed gas (containing 5% hydrogen), with a heating rate of 1℃ / min, and the temperature naturally drops to room temperature to obtain a solid powder of Ru / Mo2C material.

[0074] The calculation method is the same as that of Example 1. The mass percentage of doped metal Ru in the Ru / Mo2C material obtained in this example is 1.62%, and the mass percentage of Mo is 18.42%. The mass of doped metal Ru in this example is 8.26% of the mass of transition metal carbide Mo2C.

[0075] Example 7

[0076] This embodiment provides a Ru / Mo2C material, and the specific steps are as follows:

[0077] Take 1g of glucose (C6H 12 O6) in a 20 ml sample bottle, add 0.0247 g of ammonium molybdate ((NH4)6Mo7O 24 ·4H2O), 0.0222g of ruthenium trichloride (RuCl3·3H2O) was dissolved in 1.6mL of deionized water, and the obtained sample was stirred at room temperature for 3h. After stirring, an appropriate amount of ethanol solution was added, and the solid powder was ground into powder after rotary evaporation in batches. In a tubular furnace, a hydrogen-nitrogen mixed gas (containing 5% hydrogen) was calcined at 1000℃ for 2h with a heating rate of 10℃ / min. When the temperature naturally dropped to room temperature, the solid powder obtained was Ru / Mo2C material.

[0078] The calculation method is the same as that of Example 1. The mass percentage of doped metal Ru in the Ru / Mo2C material obtained in this example is 7.24%, and the mass percentage of transition metal Mo is 9.57%. The mass of doped metal Ru in this example is 7.08% of the mass of transition metal carbide Mo2C.

[0079] Example 8

[0080] This embodiment provides a Ru / Mo2C(1-14) material, and the specific steps are as follows:

[0081] Take 0.05g Ketjenblack EC-600JD in a 20ml sample bottle, dissolve 0.038g molybdenum pentachloride (MoCl5) and 0.0020g ruthenium trichloride (RuCl3·3H2O) in 1.6mL anhydrous ethanol solution, and mix them ultrasonically for 2h. The viscous mixture sample is placed in a vacuum oven at 70°C and dried for 12h to obtain a solid mixture. The solid mixture is ground into powder and calcined at 800°C for 2h in a tubular furnace in a hydrogen-argon mixed gas (containing 5% hydrogen) atmosphere with a heating rate of 10°C / min. When the temperature naturally drops to room temperature, the solid powder obtained is Ru / Mo2C(1-14) material.

[0082] The calculation method is the same as that of Example 1. The mass percentage of doped metal Ru in the Ru / Mo2C (1-14) material obtained in this example is 1.57%, and the mass percentage of transition metal Mo is 20.84%. The mass of doped metal Ru in this example is 7.08% of the mass of transition metal carbide Mo2C.

[0083] like Figure 8 As shown, Figure 8 is the XRD pattern of Ru / Mo2C(1-14) prepared in this example. Figure 8 It can be found that the diffraction peaks at 34.3°, 37.9° and 39.3°, which correspond to the (100), (002) and (101) crystal planes of molybdenum carbide, respectively, have decreased significantly. At the same time, the relative intensities of the diffraction peaks at 37.9° and 39.3° have also changed significantly. Figure 1 Compared with the results of , the decrease in the diffraction peak intensity indicates that the crystal structure order of MoC is significantly reduced, which indicates that Ru doping significantly reduces the structural order of MoC. Calculations based on Jade software show that the structural order is reduced by about 50%.

[0084] The materials obtained in Example 1 and Comparative Example 1 were tested as follows:

[0085] A three-electrode test system was used, the electrolyte was 1M KOH, and the CHI-760E electrochemical station was used at room temperature. Platinum foil was used as the counter electrode and Hg / HgO was used as the reference electrode. The catalyst slurry was prepared using ultrapure water and ethanol (v / v = 50:950) and a certain amount of 5wt% Nafion solution. 20μL of the catalyst slurry was placed on a glassy carbon electrode (d = 5mm, with a geometric electrode area of ​​0.196cm 2 ) and dried in air to prepare a working electrode. For Example 1, the loading amount of Mo2C on the electrode is 0.033 mg cm -2 For comparative example 1, the loading amount of Mo2C is 0.112 mg cm -2The polarization curve of hydrogen evolution reaction was obtained by linear sweep voltammetry (LSV) with a scan rate of 5 mVs -1 .

[0086] In the evaluation of the catalytic activity of hydrogen evolution reaction catalysts, the current density is generally 10 mA cm -2 The overpotential at which the catalyst is reacted is used to characterize and compare the performance of the catalyst. The standard potential of the hydrogen evolution reaction is 0 V, so the current density is 10 mA cm -2 The potential at which the catalyst reacts is called the overpotential. The smaller the overpotential, the better the hydrogen evolution reaction performance of the catalyst.

[0087] like Fig. 9 As shown, Fig. 9 It is the polarization curve diagram of Ru / Mo2C (3-12) prepared in Example 1 and Mo2C prepared in Comparative Example 1. Fig. 9 The middle curve data shows that when Mo2C in Comparative Example 1 is used for hydrogen evolution reaction at a current density of 10 mA cm -2 The overpotential at 270° reached 156 mV, while for the Ru-Mo2C(3-12) material in Example 1, this value was only 22 mV, which indicates that the order of molybdenum carbide was reduced by doping with ruthenium, thereby effectively improving its catalytic activity as a catalyst for hydrogen evolution reaction.

[0088] In addition, we used water washing to simulate the accelerated oxidation process of molybdenum carbide materials in the air, and tested the hydrogen evolution performance of Ru / Mo2C(3-12) and Mo2C materials after water washing. Carbide materials easily form a thin layer of oxide on the surface in the air, and the formation of this oxide thin layer will significantly reduce the conductivity of the carbide material, and also reduce its catalytic activity as a catalyst for hydrogen evolution reaction.

[0089] like Fig.10 As shown, Fig.10 The electrochemical polarization curves of Ru / Mo2C (3-12) prepared in Example 1 and Mo2C prepared in Comparative Example 1 before and after the oxidation resistance test. Fig.10 Middle curve data, after Mo2C material is washed, the current density is 10mAcm -2 The overpotential at the Ru / Mo2C(3-12) increased from 156mV to 517mV, and the current density was 10mAcm after washing. -2The overpotential at 22 mV increased from 28 mV, indicating that the catalytic activity of the hydrogen evolution reaction of the Ru / Mo2C(3-12) material decreased less than that of the Mo2C material, and further indicated that the formation rate of the surface oxide layer of the Ru / Mo2C(3-12) material was slower than that of the Mo2C material. The above results show that the doping of ruthenium effectively slows down the formation of the surface oxide layer of molybdenum carbide, thereby improving its oxidation resistance and stability and extending the service life of the doped material.

[0090] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A doped transition metal carbide material, characterized in that: The material comprises transition metal carbide and doped metal. Calculated by mass percentage, the mass of the doped metal is 0.1% to 50% of the mass of the transition metal carbide.

2. The doped transition metal carbide material according to claim 1, characterized in that: After doping, the long-range order of the crystal structure of the transition metal carbide changes, and the order decreases by 0.1%-100%.

3. The doped transition metal carbide material according to claim 2, characterized in that: The order of transition metal carbides is reduced by 50%-100% after doping.

4. The doped transition metal carbide material according to claim 1, characterized in that: The doping metal is selected from at least one of platinum, palladium, ruthenium, iridium, gold, rhodium, osmium, silver and chromium; the transition metal in the transition metal carbide is selected from at least one of molybdenum, iron, cobalt, nickel, vanadium, copper, zinc, tungsten and tin.

5. A method for preparing a doped transition metal carbide material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing a carbon-containing precursor, a transition metal precursor and a doped metal precursor, subjecting the mixture to a high-temperature calcination process, and then cooling the mixture to room temperature to obtain a doped transition metal carbide material.

6. The method for preparing a doped transition metal carbide material according to claim 5, characterized in that: The carbon-containing precursor is selected from any one of natural carbon materials, artificial carbon materials, various derived carbon materials or carbon-containing organic matter; the transition metal precursor is selected from any one of transition metal sulfates, transition metal chlorides, transition metal acetates, transition metal nitrates, transition metal ammonium salts, transition metal carbonyl compounds, and transition metal oxides; the doped metal precursor is selected from any one of doped metal nitrates, doped metal chlorides, doped metal acetates or doped metal sulfates.

7. The method for preparing a doped transition metal carbide material according to claim 5, characterized in that: The method of uniformly mixing the carbon-containing precursor, the transition metal precursor and the doped metal precursor is at least one of a grinding method, an impregnation method, an ultrasonic mixing method or a rotary evaporation method.

8. The method for preparing a doped transition metal carbide material according to claim 7, characterized in that: The solvent used in the immersion method, ultrasonic mixing method and rotary evaporation method is selected from at least one of water, ethanol, methanol, acetone, ethylene glycol or isopropanol.

9. The method for preparing a doped transition metal carbide material according to claim 5, characterized in that: The conditions of the high temperature calcination process are: calcination at 400°C to 1200°C in a specific atmosphere for 0.5h to 48h; The specific atmosphere is selected from any one of hydrogen, carbon monoxide, or a reducing mixed atmosphere.

10. The method for preparing a doped transition metal carbide material according to claim 9, characterized in that: The reducing mixed atmosphere comprises reducing gas and balancing gas, wherein the volume concentration of the reducing gas is 5%-45%; the reducing gas is selected from any one of hydrogen or carbon monoxide, and the balancing gas is selected from any one of argon, nitrogen and helium.